Early versus newer generation transcatheter heart valves for transcatheter aortic valve implantation: Echocardiographic and hemodynamic evaluation of an all-comers study cohort using the dimensionless aortic regurgitation index (AR-index) - Stundl, Anja (PLoS One, 2019)
AIMS: More than mild paravalvular aortic regurgitation (pAR) negatively impacts prognosis after transcatheter aortic valve implantation (TAVI). “Newer generation” transcatheter heart valves (THVs) including Direct Flow Medical, Medtronic Evolut R, Boston Lotus, and Edwards SAPIEN 3 valve system promise to improve outcome by reducing the rate of TAVI-related issues such as pAR. Aim was to evaluate and compare the hemodynamic performance with AR index of “early” vs. “newer generation” THVs and its impact on outcome. METHODS AND RESULTS: In 805 patients undergoing TAVI, the degree of pAR was assessed using imaging modalities (angiography, echocardiography) and hemodynamic measurements (aortic regurgitation index, ARI ratio). Severity of pAR and outcome were assessed according to the VARC-2 criteria. 805 patients underwent TAVI with use of the CoreValve (n = 400), SAPIEN XT (n = 48), Direct Flow Medical (n = 38), Evolut R (n = 114), Lotus (n = 104), or SAPIEN 3 (n = 101) prosthesis. TTE post TAVI revealed that a total of 7.3% of the patients showed moderate/severe pAR. The occurrence of greater than mild pAR occurred less frequently in patients treated with “newer generation” THVs (p<0.001): CoreValve (11.3%), SAPIEN XT (12.5%), Direct Flow Medical (5.3%), Evolut R (5.3%), Lotus (0.0%), and SAPIEN 3 (0.0%). The AR index was significantly higher (p<0.001) in patients receiving “newer generation” prostheses compared to those in whom “earlier generation” THVs were used. However, the ARI was only predictive of cumulative all-cause mortality at 1 and 3 years in “early generation”, but not in “newer generation” THVs. In the overall cohort, 30-day and 1-year mortality was 4.8% and 20.1%, respectively. In patients treated with “newer generation” devices, the respective mortality rates remained substantially below those of patients treated with “earlier generation” THVs (30-day mortality: 2.5% vs. 6.7%, p< 0.001; 1-year mortality: 11.2% vs. 27.2%, p<0.001). CONCLUSION: TAVI with use of “newer generation” THVs showed significantly reduced pAR and improved outcomes compared to “early generation” devices that could at least in part be explained by more favorable hemodynamics